On Inhabiting Monastic Heritage: Monastery “Nieuw Sion” in the Netherlands as Material Burden and Spiritual Opportunity - Wouter Kock; Eric Venbrux; Thomas Quartier (Religions)
For decades, the Catholic monastic tradition has been defined by demographic decline and the closure of monasteries. And yet, new religious groups have emerged that have cultivated their own take on the monastic tradition, while old monasteries have become treasured heritage objects. In recent years, these new religious groups have started to acquire and inhabit old monasteries. It follows that simultaneous re-religionization and heritagization is taking place at these locations. This combination presents a unique opportunity to scrutinize an unexplored entanglement of religion and heritage. Although re-religionization might seem to conflict with the cultural heritage narrative surrounding these monasteries, this article presents Klooster Nieuw Sion—a new Dutch religious initiative—as a case study, indicating that these developments do not only coexist or oppose each other but are also mutually reinforcing. Drawing on our fieldwork, we explore how heritagization can offer new spiritual opportunities for religious actors within these revitalized monastic spaces.